PENDAMPINGAN PELAKSANAAN PROGRAM PENGEMBANGAN UMKM PABRIK TAHU H. RIYADI DALAM MENUNJANG REVOLUSI INDUSTRI 4.0 DENGAN TRANSFORMASI DIGITAL DI KABUPATEN BOJONEGORO - Astuti, Hartiningsih; Susilo, Joko Hadi; Ramadani, Febiola Djangkaru; Anggraini, Arieta Mudrika (Universitas Kadiri, 2025)
This mentoring was motivated by the challenges faced by the Tahu H. Riyadi Micro, Small, and Medium Enterprises (MSMEs) in adopting digital transformation in the Industrial Revolution 4.0 era. The main problems include a lack of understanding about the importance of using digital payment methods and sustainable waste management. The purpose of this mentoring is to increase awareness and ability of MSMEs in implementing the digital payment system, namely QRIS, with support in the form of creating Instagram social media as a supporting medium, as well as educating about environmentally friendly waste management. The scientific contribution from the results of this community service is expected to provide new insights in the development of science and technology, especially in the application of digital technology in the MSME sector. The methods used in this mentoring include observation, interviews, socialization, and active participation. The results of the mentoring show that the partners successfully implemented the QRIS system, which increased transaction efficiency and provided convenience for consumers. In addition, socialization regarding waste management succeeded in raising awareness of the importance of the environment, with several management steps that have been implemented. Targets achieved include ease of transactions with a 40% increase in digital transactions and a reduction in inorganic waste that is disposed of carelessly. The results of this mentoring not only provide direct benefits to the MSMEs concerned, but also contribute to efforts to improve sustainable knowledge and practices in the community to support the development of Industry 4.0.